2010
DOI: 10.1007/s11418-010-0388-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and synergistic effects of Smallanthus sonchifolius leaf extracts against methicillin-resistant Staphylococcus aureus under light intensity

Abstract: Smallanthus sonchifolius (yacon) is a perennial plant mostly cultivated in South America, primarily for use of the tubers as a food crop and the leaves as fodder for livestock. The antibacterial activities of the methanol extract of yacon leaves (S. sonchifolius) and its n-hexane, ethyl acetate, n-butanol and water fractions were evaluated against 6 strains of methicillin-resistant Staphylococcus aureus (MRSA) and 1 standard methicillin-susceptible S. aureus (MSSA) strain by using the disc diffusion method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
0
10
0
4
Order By: Relevance
“…Moreover, findings from the present study showed that AEBv was effective against a methicillin-resistant strain of S. aureus (MRSA). These MRSA are difficult to treat because they are also multiresistant and up to now there are no satisfactory antimicrobial drugs (Joung et al 2010). Therefore, regarding to the present result, extract from B. virgilioides seem to be a potential tool to combat the problem of MRSA.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, findings from the present study showed that AEBv was effective against a methicillin-resistant strain of S. aureus (MRSA). These MRSA are difficult to treat because they are also multiresistant and up to now there are no satisfactory antimicrobial drugs (Joung et al 2010). Therefore, regarding to the present result, extract from B. virgilioides seem to be a potential tool to combat the problem of MRSA.…”
Section: Discussionmentioning
confidence: 63%
“…As Standards (2003). A modified diffusion test was used to determine the antimicrobial activity (Joung et al 2010). The colonies were taken directly from the plate and were suspended in 5 mL of sterile 0.85% saline.…”
Section: Plant Materials and Preparationsmentioning
confidence: 99%
“…Studies have reported that yacon also presents antioxidant activity related to compounds such as flavonoids (Arnao et al 2011), phenolic acids (Castro et al 2012), and tryptophan (Yan et al 1999), beyond anti-inflammatory (Honoré et al 2012), anti-obesity (Hasani-Ranjbar et al 2013), antibacterial (Joung et al 2010), antifungal (Yun et al 2012), and anticancer (Moura et al 2012) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Under light illumination at 4,000 lux for 18 hours, the n-hexane fraction of yacon leaf methanol extract showed antibacterial effect against six strains of methicillin-resistant Staphylococcus aure us (MRSA) and one standard methicillin-susceptible S. aureus (MSSA) with a MIC of 15.6 μg/mL (Joung et al 2010 ). No activity was detected in the absence of light.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Smallanthus sonchifolius (yacon) is a perennial plant mostly cultivated in South America, primarily for use of the tubers as a food crop and the leaves as fodder for livestock (Joung et al 2010 ).…”
Section: Other Usesmentioning
confidence: 99%